Search for pair production of Higgs bosons in the bb¯bb¯ final state using proton--proton collisions at s√=13 TeV with the ATLAS detector - Aaboud, M. (2016)
A search for Higgs-boson pair production in thA search for Higgs-boson pair production in the bbb¯ b¯ final state is carried out with 3.2 fb−1 of proton–proton collision data collected at √ s = 13 TeV with the ATLAS detector. The data are consistent with the estimated background and are used to set upper limits on the production cross section of Higgs-boson pairs times branching ratio to bbb¯ b¯ for both nonresonant and resonant production. In the case of resonant production of Kaluza–Klein gravitons within the Randall–Sundrum model, upper limits in the 24 to 91 fb range are obtained for masses between 600 and 3000 GeV, at the 95% confidence level. The production cross section times branching ratio for nonresonant Higgs-boson pairs is also constrained to be less than 1.22 pb, at the 95% confidence level.